Eletrolite leakage as a technique to diagnose euphorbia heterophylla biotypes resistant to ppo-inhibitors herbicides - Trezzi,M.M (2011)
The action of herbicides that affect the integrity of cell membranes and cause leakage, like PPO-inhibitors, can be detected by measuring the electric conductivity (EC) of a solution in which the plant tissue target is incubated in the presence of herbicide. The objectives of this work were to confirm PPO resistance in a new Euphorbia heterophylla (EPHHL) biotype, and to compare the electrolyte leakage from R and S to PPO-inhibitors biotypes, using two different methods of incubation in a solution containing herbicides. One experiment was carried in greenhouse and three in laboratory, with a completely randomized design. In the greenhouse experiment, four biotypes of EPHHL were sprayed with seven rates of fomesafen to confirm resistance in suspected biotypes. Leaf disks from R and S EPHHL biotypes in the second and the third experiments and entire leaves in the fourth experiment were incubated in a solution containing PPO-inhibitors to subsequently determine EC of solution. The study confirmed the resistance to PPO-inhibitors in two EPHHL biotypes. There were no significant differences between S and R biotypes in the experiments with the incubation of leaf disks, but incubation of entire leaves of EPHHL S biotype showed higher EC when in a solution with fomesafen, in comparison to the R biotype. The results of this work are an indirect evidence that resistance to PPO-inhibitors is related to lower absorption of herbicide by the shoots and also to some kind of mechanism to cope with oxidative stress.